INCIDENCIA DE CISTICERCOSIS PORCINA EN EL DISTRITO DE MATAPALO, TUMBES - Mena A., Carlos (2004)
It was evaluated the prevalence and the incidence rate (force of morbidity of cysticercosis) in the period of January-April, 2000 in the porcine population of Matapalo’s village (Zarumilla, Tumbes). In the first sampling, 922 animals older than 3 months were evaluated and 284 resulted positive representing a prevalence of 30.8 ± 3.0% . The second sampling, carried out three months later on 778 animals reported a prevalence of 20.8 ± 2.9%. A total of 314 negative animals at the first sampling were evaluated in the second sampling and 36 seroconverted to the EITB test resulting in an accumulated incidence of 11.5 ± 3.5%. A number of risk factors were analyzed for the prevalence of porcine cysticercosis finding out that village, age and sampling represented a factor of risk to find a positive animal. Similarly, several factors relating to incidence were analized and was found that the variables village, age, immunological condition of the mother, and sex represented risk factors to get the disease.